Plan de negocios para la creación del almacén tallas grandes, en Manizales (2013)
Every human being overweight and to meet your needs you need to target your tastes and whims in their clothing large sizes, making it becomes much more interesting the project. administrative school of Henry Fayol explained through the classical school where the planning, organizing, directing, executing and controlling a company is part of the overall objective of this project and forms the rationale for all types of business organization, using the functions perform basic operations in different administrative areas, commercial and operational. Research tools that support this investment project, are surveys, contacts, and secondary information, which are expected to find concrete solutions to marketing problems, marketing and internal structure of the garments trading company sizes. The technical study allowed establishing requirements for technology, tools, equipment, location, size and infrastructure. According to the results given in the surveys are necessary to create a store that specializes in clothing for obese people to meet the need of this target market.